Perancangan Sistem Informasi Geografis Berbasis Web dengan Geotagging untuk Pengaduan Masyarakat dan Pendataan Kerusakan Infrastruktur - Denhaz Pattra Affiza; Dahlan Abdullah; Muthmainnah Muthmainnah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Maintenance of public infrastructure such as potholed roads, damaged bridges and malfunctioning lighting is often hampered by the absence of a fast, accurate and location-based reporting system. This results in a slow response from relevant agencies in dealing with the damage. This research aims to design and develop a web-based Geographic Information System (GIS) equipped with geotagging features to facilitate digital and spatial reporting of infrastructure damage. The system was developed using the Waterfall method through the stages of analysis, design, implementation, and testing. The technologies used include Laravel, JavaScript, HTML, CSS, and OpenStreetMap. The main features of the system include a reporting form with automatic geotagging, an interactive map, and an admin dashboard for the verification process. Testing was conducted using the Black Box and User Acceptance Test (UAT) methods, which resulted in 90% efficiency, 87% service, and 81% design scores. These results show that the designed system is able to improve reporting efficiency and strengthen community participation. This system is expected to be a participatory and transparent technology solution in managing and handling public infrastructure more quickly and responsively.